A New Augmentation Strategy against Depression Combining SSRIs and the N-terminal Fragment of Galanin (1-15) - Flores-Burgess, Antonio; Millón, Carmelo; Cantero-García, Noelia; Pineda-Gómez, Juan Pedro; Flores-Gómez, Marta; Díaz-Cabiale, Zaida (Current Neuropharmacology, 2025)
Depression is one of the most disabling mental disorders, with the second highest social burden; its prevalence has grown by more than 27% in recent years, affecting 246 million in 2021. Despite the wide range of antidepressants available, more than 50% of patients show treatment-resistant depression. In this review, we summarized the progress in developing a new augmentation strategy based on combining the N-terminal fragment of Galanin (1-15) and SSRI-type antidepressants in animal models.
Keywords: antidepressants